Strategi Guru Bimbingan Konseling Memfasilitasi Siswa Kelas X Mengatasi Career Indecision Tahap Eksplorasi Karir SMA Negeri 2 Lubuk Basung - Siska Muliasari; Irman I (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The implementation of the Merdeka Curriculum at the Senior High School (SMA) level requires Grade X students in Phase E to begin planning their career paths early, as these decisions directly affect subject selection in Grade XI Phase F. In practice, Grade X students who are in the adolescent developmental stage often experience career indecision due to limited self-understanding, lack of career information, and the influence of family and social environments. This study aims to describe the strategies employed by guidance and counseling (BK) teachers in facilitating Grade X students to overcome career indecision during the career exploration stage at SMA Negeri 2 Lubuk Basung. The study adopts a descriptive qualitative approach with a field research design. The research informants consisted of one BK teacher as the main informant and five Grade X Phase E students as supporting informants. Data collection techniques included observation, interviews, and documentation. Data analysis was conducted through data reduction, data presentation, and conclusion drawing and verification. Data validity was ensured through source, technique, and time triangulation. The findings indicate that BK teachers’ strategies in addressing career indecision include career information services, individual and group counseling, career guidance integrated into school activities, and collaboration with parents and subject teachers. The use of information technology, such as application-based interest and aptitude assessments, also helps students recognize their potential and determine appropriate career directions. Despite facing constraints related to limited time and facilities, the strategies implemented by BK teachers are able to reduce students’ career indecision and enhance their readiness for career decision-making at the exploration stage.